Effect of dietary nutrient profile on plasma glucagon-like peptide-2 in healthy cats - Freilich, Leah (Kansas State University, 2022)
Glucagon-like peptide-2 (GLP-2) is a meal-induced enteroendocrine hormone responsible for intestinal mucosal growth and repair. GLP-2 secretion in humans and rodents is nutrient-dependent with differential plasma concentrations based on the major nutrient component of a meal. Pre- and post-prandial concentrations of plasma GLP-2 have not been measured in cats. A feasibility study was performed which evaluated whether GLP-2 could be measured in the plasma of client-owned cats, with the secondary hypothesis that the addition of proteinase inhibitor to the plasma samples immediately after collection would increase measured concentrations of GLP-2. A subsequent nutritional study investigated plasma concentrations of GLP-2 in 9 healthy research cats after a fixed calorie meal high in carbohydrates, protein, or fat, with the hypothesis that maximal GLP-2 plasma concentration would occur 30 minutes after the meal, and a high-fat meal would lead to increased plasma GLP-2 concentrations compared to a high-protein or high-carbohydrate meal. In the feasibility study, plasma samples were obtained from 6 fasted client-owned cats at baseline and then one hour after a standardized meal. In the nutritional study, 9 healthy research cats were fasted prior to being fed a calorically standardized meal of 3 different commercial diets relatively high in carbohydrates, protein, or fat. Blood samples were collected at baseline, 30, 60, 75, 90, and 120 minutes after finishing the meal. For both studies, two proteinase inhibitors were added to half of the blood sample immediately after collection. Plasma GLP-2 concentrations were measured using a commercial ELISA. Pre- and post-prandial GLP-2 concentrations and the concentrations of GLP-2 with and without proteinase inhibition were compared using a paired t test. The Friedman test and one-way ANOVA of repeated measures were used to evaluate maximal secretion of GLP-2 within each diet, for non-normally distributed data and normally distributed data, respectively. A mixed analysis of variance with repeated measures was used to evaluate effect of diet on GLP-2 concentrations over time. GLP-2 was detected in all samples. There was no difference between measured GLP-2 concentrations with versus without proteinase inhibitor in either study. Mean GLP-2 concentration 30 minutes after the high-fat meal (1.64 ± 0.23 ng/mL) was significantly higher than at 90 minutes (1.39 ± 0.31 ng/mL; P = 0.029) or 120 minutes (1.44 ± 0.27 ng/mL; P = 0.031) but not significantly different than baseline (1.49 ± 0.28 ng/mL; P = 0.085). There was no difference in pre- or post-prandial GLP-2 concentrations among the high-carbohydrate or high-protein meals. The results of this study suggest that a meal high in fat provides a stimulus for GLP-2 secretion in cats, while meals high in protein and carbohydrate do not. Proteinase inhibition does not affect GLP-2 measurement using this commercial ELISA.
Keywords: Enteroendocrine; Glucagon-like peptides; Feline